Spatial and temporal distribution of Diatraea spp. (Lepidoptera: Crambidae) in the Cauca River Valley, Colombia - Leyton-Flor, Samy Andrés; Gordillo, Marisol; González, Paula A.; Ospina, Johann A.; Vargas, Germán (Revista Colombiana de Entomología, 2018)
Sugarcane stem borer (Diatraea spp) damage has increased in the Cauca River Valley (CRV) due to two new species, D. tabernella and D. busckella, which joined the two already known species, D. saccharalis and D. indigenella. A study of the bioecology of these pests and their natural enemies is presented in order to increase the effectiveness of pest management, which consists primarily of biological control. An assessment of the extent of pest damage was completed during a crop cycle in nine fields distributed along the CRV. Sampling was done in a 30x30 meter grid and 50 points were geo-referenced in each field. A registry was made of the number of damaged stalks and the number of bored internodes per stalk. Outside the grid, eggs and larvae of the pests were collected by means of a one man-hour sampling effort. The northern CRV showed the greatest levels of pest injury and a predominance of D. tabernella and D. busckella. Egg parasitism by Trichogramma exiguum reached levels of 98 %, whereas Cotesia flavipes was the most abundant larval parasitoid. There were positive correlations between the percent of damaged stalks (%TD) and crop age, and between the number of larvae and parasitized larvae. A spatial analysis of %TD showed an aggregated distribution concentrated toward the edge of the grid. Pest management protocols should be differentiated by region within the CRV in order to prioritize areas of greatest infestation.